Theory of Planned Behavior: Analysis of Factors Affecting the Preventive Behaviors of Alcohol Consumption and Smoking among Students from West Kalimantan, in Yogyakarta - Yesi Vila Delpia; Bhisma Murti; Nunuk Suryani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Indonesia ranked the third highest country in the world in the prevalence of smokers in 2010. The prevalence of alcohol drinkers reached 4.6% in 2007. West Kalimantan ranked the third highest and the fifth highest province in Indonesia in the number of smokers and drinkers, respectively. This study aimed to analyze factors affecting the preventive behavior of alcohol consumption and smoking among students from West Kalimantan, Indonesia.Subjects and Method: This was an analytical observational study with cross sectional design, conducted in Yogyakarta. A total of 100 students of West Kalimantan were selected by simple random sampling. The data were collected by a set of questionnaire and analyzed by path analysis.Results: Positive attitude toward alcohol consumption (b=0.196; p=<0.001), positive subjective norms (b=0.650; p <0.001), strong perceived behavior control (b=0.296; p=<0.001), strong intention (b=1.755; p <0.001) had positive effect on alcohol consumption preventive behavior. Positive attitude toward smoking (b=0.381; p <0.001), positive subjective norms (b= 0.357; p< 0.001), strong perceived behavior control (b=0.252; p <0.001), and strong intention (b =1.122; p< 0.001) had positive effect on smoking prevention behavior.Conclusion: Theory of planned behavior can be used to predict preventive health behavior of a person, with respect to alcohol consumption and smoking. Attitude, subjective norm, perceive behavior control, and intention, each had either indirect or direct effect on alcohol consumption and smoking prevention behavior.Keywords: Theory of Planned Behavior, alcohol consumption, smoking, preventive behaviorCorrespondence: Yesi Vila Delpia. Masters Program in Public Heath, Sebelas Maret University, Surakarta. Email: yesiviladelpia137@gmail.com.Journal of Health Promotion and Behavior (2016),1(2): 62-69https://doi.org/10.26911/thejhpb.2016.01.02.01